A scalable polymer-free method for transferring graphene onto arbitrary surfaces. (May 2020) - Zhang, Xuewei; Xu, Chen; Zou, Zhenxing; Wu, Zehao; Yin, Shaoqian; Zhang, Zilong; Liu, Jinglan; Xia, Yang; Lin, Cheng-Te; Zhao, Pei; Wang, Hongtao
Abstract: An efficient and reliable transfer for graphene onto the substrates of interests acts as the crucial bridge between the graphene synthesis and applications. The main reason that this issue has not been fully addressed is the use of a polymer medium to protect the one-atom-thick material during the transfer process. Here we demonstrate a general and scalable method to transfer chemical-vapor-deposited graphene onto arbitrary surfaces without any polymers, which yields the transfer of macroscopically and microscopically clean, continuous and uniform graphene samples onto a wide variety of substrates, as well as the scalable layer-by-layer graphene epitaxial structures. Moreover, the transferred graphene exhibits an overall 100% enhancement in the electrical conductivity compared with the conventional method, so that various high-performance flexible transparent electrodes can be demonstrated. We believe that this new transfer technique will offer the opportunities to the industrialization of next generations of flexible electronics and other graphene-based disruptive technologies. Graphical abstract: Image 1